An assessment of procedures and techniques employed by manufacturing organisations in the Port Elizabeth/Uitenhage region to evaluate the effectiveness of their supervisory training - Berry, David Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.